Proses Komunikasi Antar Budaya Antara Pedagang Lokal Dengan Wisatawan Asing Di Pantai Kuta, Bali - Syifa Sri Amanda; Ridma Meltareza (Komunika : Jurnal Ilmiah Komunikasi, 2025)
Interacting with people from diverse cultural backgrounds can be a barrier to intercultural communication. This research aims to understand the intercultural communication process, the variables that facilitate it, and the various barriers and communication adaptation techniques faced by local vendors on Kuta Beach, Bali, when interacting with foreign tourists. Kuta Beach was chosen as the research location because it is an international tourism area with a high level of transactional intercultural interaction. The study implemented a qualitative research approach, utilizing focused ethnographic methods. Data were collected using several techniques, including direct observation, interviews, and documentation with five key informants, local vendors, and three supporting informants, including foreign tourists. Data analysis used thematic analysis, referring to Miles and Huberman's interactive analysis model and Chaney and Martin's framework of intercultural communication barriers. The research findings show that the communication process between local vendors and foreign tourists occurs through a combination of limited verbal communication and dominant nonverbal communication. The communication barriers identified include physical, cultural, perceptual, motivational, experiential, emotional, linguistic, nonverbal, and competitive barriers. To overcome these obstacles, local vendors independently developed adaptive communication strategies, such as using simple English, body gestures, friendly expressions, and utilizing communication aids. This research emphasizes the importance of intercultural communication skills for local vendors in supporting tourism interactions in the Kuta Beach area, Bali.